THE EFFECT OF SPUTTERING TEMPERATURE OF TiO2/ITO-PEN PHOTOANODES IN DYE SENSITIZED SOLAR CELL - Ma'arifah, Alfiatul; Sholeha, Nabella; Nurhamidah, Millah; Diningsih, Ridha; Pujiarti, Herlin (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Currently, the world is facing a major crisis related to the lack of sustainable, safe, and environmentally friendly energy resources. Dye sensitized solar cells (DSSC), another name for third-generation solar cells, have gained a lot of interest due to ease of production, cheapness, and environmental friendliness. The photoanode is among DSSC's most crucial components. In this research, the active layer on the TiO2 photoanode was optimized to improve the efficiency of the DSSC. The active layer was deposited using Radio Frequency (RF) magnetron sputtering on an Indium tin oxide-polyethylene naphthalate (ITO-PEN) substrate. The sputtering temperature was varied to 25, 80, 120, and 160℃ for one hour. The thin film TiO2/ITO-PEN photoanode will be characterized by means of X-ray Diffraction (XRD), Ultraviolet-Visible (UV-Vis) spectroscopy, and solar simulator. The XRD analysis shows that the best crystal size is 14.55 nm for a sputtering temperature of 80℃. According to the UV-Vis data, optical absorption increases with increasing sputtering temperature. The wavelength range where the absorption peak occurs is 252–465 nm, and the smallest value of the energy gap is found at a sputtering temperature of 25℃ with a value of 3.02 eV. For the TiO2/ITO-PEN thin layer, the maximum efficiency was achieved at 0.12% at a sputtering temperature of 25°C.